East Java: Cenozoic basins, volcanoes and ancient basement - Smyth, H.; Hall, R.; Hamilton, Joseph; Kinny, Peter (Indonesian Petroleum Association, 2005)
East Java on land is divided here into four broadly EW zones: (1) the Southern Mountains Zone, an Eocene to Miocene volcanic arc, separated by (2) the present-day volcanic arc from (3) the Kendeng Zone which was the main Cenozoic depocentre in onshore East Java; and to the north (4) the Rembang Zone which represents the edge of the Sunda Shelf. Several synthems separated by unconformities can be identified and correlated between the different zones. There is a regional angular unconformity above Upper Cretaceous and older basement. The oldest rocks above the unconformity range from Mid Eocene to Lower Oligocene and record a gradual transgression and, in SE Java, an increase in volcanic material up-section.After an intra-Oligocene sea-level fall, volcanic material from the arc dominated in the Southern Mountains and Kendeng Zones while in the Rembang Zone carbonate deposition continued. In the Early Miocene, activity in the Southern Mountains Volcanic Arc culminated in a major eruptive phase at 20 Ma ± 1 Ma, similar in scale to the Pleistocene eruptions of Toba. To the north carbonate deposition was interrupted by clastic input containing reworked basement and Eocene material. The Mid Miocene was a period of reworking and carbonate sedimentation. In the Late Miocene volcanic activity recommenced at the position of the present-day arc and there was a series of deformation events throughout East Java. Volcanism has played an important role in the development of East Java, providing a source of material and contributing to subsidence by flexural loading. Provenance studies and dating of zircons provide insight into the basement character and suggest that continental crust of Gondwana (possibly Western Australian) origin lies beneath part of the Southern Mountains Zone. It is suggested that continental Sundaland provided very little, if any, terrigenous material to East Java in the Cenozoic.